Paryska „Kultura” wobec wybranych wydarzeń z historii stosunków polsko-ukraińskich z lat 1919-1947 - Komoński, Ernest (Acta Universitatis Lodziensis. Folia Historica, 2008)
Jerzy Giedroyc (1906-2000) was an editor of the Polish emigré monthly “Kultura" (1947-2000). He created interesting and influential periodical presently regarded as an only independent centre of Polish political thought after the Second World Was. Within activity of the monthly there were initiatives and ideas how Poland should develop the relationships with its neighbours, especially with Ukraine. In the view of “Kultura” Ukraine as a future independent country should be strongly related with Poland. Owing to this Poland could depend on partner relations with Russia. Both Polish and Ukrainian publicists of “Kultura” showed the ways how to create the future agreement between Poland and Ukraine. The one of its crucial links could be honest and free of communist or nationalist rhetoric explanation of the events from common twentiethcentury history. Jerzy Giedroyc’s circle considered it as an element of bilateral conciliation. Publicists of “Kultura” wrote several articles on the Polish policy towards the Ukrainians in interward Poland. In this topic there was emphasized unequal treatment of Ukrainian allies by Poles during Polish-Bolshevik war (1919-1921) and proved discrimination against the Ukrainian minority by the Polish government in the 30s. The Second World War (1939-1945) brought especially many dramatic events in Polish- Ukrainian history. Paris “Kultura wished to explicate a few problems. The first one was a question of political and practical responsibility for the death of Polish professors from Lvov in 1941. The second one was an issue of mass murder of Polish inhabitants of Volhynia and East Galicia committed by a part of Ukrainian nationalises in 1942-1944. In “Kultura” very important were articles on widespread stereotypes of military supporting German Nazis by Ukrainian nationalists during the putting down of the Warsaw Uprising in 1944. Other crucial topic was a problem of cooperation of Polish and Ukrainian underground troops against the communist regime shortly after the Second World War in the area of contemporary Poland. The subject of twentieth-century Polish-Ukrainian history was relatively often presented in “Kultura” and its “Zeszyty Historycznc". The specific of it among other things has consisted in describing historical events according to Anglo-Saxon terminology in the humanities. The informative purpose of “Kultura” in explaining problems from common history in several cases was eclipsed by the didactic purpose - Paris “Kultura” consciously hyperbolized the examples of Polish-Ukrainian cooperation because in Giedroyc’s conviction such a tactics would facilitate neighbourly conciliation. Other, definitely less controversial Giedroyc’s publicists’ work was created to Polish and Ukrainian historians a platform of understanding and friendly climate for research into mutual history.